The role of nicotine replacement therapy for temporary abstinence in the home to protect children from environmental tobacco smoke exposure: a qualitative study with disadvantaged smokers - Atkinson, Olesya; Coleman, Tim; McNeill, Ann; Lewis, Sarah; Jones, Laura L. (BioMed Central, 2013)
Background Nicotine replacement therapy (NRT) has recently been licensed to help smokers to abstain from smoking for short time periods and recent studies have shown that 8-14% of smokers are regularly using NRT to cope when they cannot or are not allowed to smoke. These data suggest that, potentially, NRT for temporary abstinence might be an acceptable method to help smoking caregivers, who are not able to stop smoking completely, to avoid smoking whilst inside their home in order to protect their children from the harms of environmental tobacco smoke (ETS). The aim of this study was therefore to explore the concept of using NRT for temporary abstinence in the home, to protect children from exposure to ETS.